Reducing Anthropology - Reyes Escate, Luis (2020)
The present paper is conceived as an analysis of the ontological implications that the irruption of anthropology degree programs, which have historically occupied the native’s point of view, have in Anthropology. A special effort is necessary in order to avoid the dead-end of reflecting on this subject as a mere issue of identity. The proposal presented herein offers a pragmatically and jointly reflection through the metatheories elaborated by minor anthropological practices, such as Roy Wagner’s reverse anthropology, Viveiros de Castro’s and Goldman’s symmetrical anthropology, Favret-Saada’s method of being affected, and Pierre Clastres’ other ethnology (non-classical). Through a symmetrical dialogue between these proposals and the philosophical concepts of Isabelle Stengers, “practices” and “etho-ecology”, and Gilles Deleuze, “operation of reduction” and “becoming”, this proposal seeks to denature and reduce Anthropology. That is, to subtract from it the great aprioristic divisions in which it stand, such as “nature-culture” and “anthropologist-native”. Thus generating opportunities that would lead us to an ontological pluralization of the anthropological practices.